2013
DOI: 10.1002/asia.201300297
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Structure Effects on Chiroptical Properties of Polyisocyanides Carrying Proline Pendants

Abstract: Chiral polymers with simple chemical structures and high helical conformation stabilities are important for their applications as chiral supports and asymmetrical catalysts. We report herein the synthesis of a series of aliphatic polyisocyanides carrying proline pendants of different chiralities, and an investigation of the effects of the chemical structures of these pendants on the chiroptical properties of the polymers. The configuration of the chiral center at the 4-position of the proline pendants was chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The resultant hybrid materials with covalently grafted chiral helical polyacetylene chains showed fascinating optical activity and were further used as chiral inducers toward enantioselective crystallization of alanine enantiomers, achieving a high enantiomeric excess value. Besides polyacetylenes, many other helical polymers, including polyisocyanate, polyguanidines, polyisocyanides, as well as sterically restricted poly(methacrylate ester)s and poly(aryl vinyl)s were synthesized and reported to be utilized in many areas one after another.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant hybrid materials with covalently grafted chiral helical polyacetylene chains showed fascinating optical activity and were further used as chiral inducers toward enantioselective crystallization of alanine enantiomers, achieving a high enantiomeric excess value. Besides polyacetylenes, many other helical polymers, including polyisocyanate, polyguanidines, polyisocyanides, as well as sterically restricted poly(methacrylate ester)s and poly(aryl vinyl)s were synthesized and reported to be utilized in many areas one after another.…”
Section: Introductionmentioning
confidence: 99%
“…Although some investigations have been carried out in recent decades, the number of artificial polymers with stable helical conformation is still limited. Examples of such artificial helical polymers include sterically restricted poly(methacrylate ester)s and poly(aryl vinyl)s, polyisocyanides, polyisocyanate, polyguanidines, and polyacetylenes . Among them, polyisocyanides have attracted considerable research interests in recent years owing to their unique fascinating rigid helical structures and wide applications in many fields .…”
Section: Introductionmentioning
confidence: 99%
“…Well-defined polyisocyanides can be obtained through the polymerization of appropriate isocyanide monomers with transition metal complexes as catalysts or initiators. The nickel(II) complex is by far the most used catalyst for the isocyanide polymerization; even the Ni(II) species reside on a polymer chain end. , We found that the Ni(II)-terminated regioregular poly(3-hexylthiophene) can initiate the living polymerization of isocyanide, affording well-defined conjugated block copolymers with controlled molecular weights and tunable compositions . However, polyisocyanides prepared with Ni(II) complexes usually possess low stereoregularity, which is important to the optical activity of a helical polymer .…”
Section: Introductionmentioning
confidence: 99%
“…However, few examples of metal-pyridine-2,5-dicarboxylate compounds containing oxalate ligand have been reported so far 12,13 . In this work, we reported a novel Zn(II) complex [Zn 2 (Hpdc) 2 (Ox)(H 2 O) 4 ] with 3D-supermolecular structure based on hydrogen bonding and π-π stacking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of ligand combines the advantages of both organic multicarboxylic acid and hetero aromatic compound. Pyridine-2,5-dicarboxylic acid (pdc) is one of such typical examples due to the chelating ability of carboxylic acid and heterocyclic nitrogen group in the chelating mode to catch various metal ions to be amenable to the formation of extended coordination complex structures [2][3][4][5][6][7][8][9][10][11] . However, few examples of metal-pyridine-2,5-dicarboxylate compounds containing oxalate ligand have been reported so far 12,13 .…”
Section: Introductionmentioning
confidence: 99%